1994
DOI: 10.1093/fampra/11.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lipid Concentrations and Other Cardiovascular Risk Factors Among Saudis

Abstract: A study of 1005 family practice attenders at King Fahad National Guard Hospital was conducted during February 1993 to determine the prevalence of hyperlipidaemia and its association with participants' sociodemographic characteristics and clinical problems. The percentage of patients with total serum cholesterol concentration (TSCC) of 5.2-6.8 mmol/l was 39.3%, while those with TSCC exceeding 6.8 mmol/l was 9.5%. Hypertriglyceridaemia (TG > 2.5 mmol/l) was found in 5%. TSCC increased progressively with age up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…We have previously reported a 17.1% rate of clinically significant obesity (BMI ≥ 30 kg/m 2 ) in Saudi males (mostly tribal men) in Riyadh. 15 That study included tribal males who had recently moved to the suburbs of Riyadh, attending the primary care center linked to a tertiary care hospital. The striking difference in prevalence might reflect different lifestyles among the two populations, especially in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported a 17.1% rate of clinically significant obesity (BMI ≥ 30 kg/m 2 ) in Saudi males (mostly tribal men) in Riyadh. 15 That study included tribal males who had recently moved to the suburbs of Riyadh, attending the primary care center linked to a tertiary care hospital. The striking difference in prevalence might reflect different lifestyles among the two populations, especially in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that hypertension and its related clinical events, such as myocardial infarction and stroke, appear to be increasing, although at a lower rate than in other parts of the world. [4][5][6][7][8] The objective of this study is to investigate the patterns of systolic and diastolic blood pressure (BP) in household random samples of the Saudi population. No study has been undertaken which covers the entire population of the Kingdom and this led us to initiate the present study.…”
Section: Al-nozha Ms Ali Ak Osman Arterial Hypertension In Saudmentioning
confidence: 99%
“…[9] In Saudi Arabia, hypertension is increasing in prevalence affecting more than one fourth of the Saudi population. [10][11][12][13][14] This increase is attributed to several factors such as lifestyle changein Saudi Arabia towards urbanization, unhealthy dietary habits, and obesity. Epidemiological studies worldwide has shown that increased awareness, follow up and control of HTN has resulted in a decreased tendency to morbidity and mortality from cardiovascular disease among hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%